Inoculum effects of cefepime/zidebactam (WCK 5222) and ertapenem/zidebactam (WCK 6777) for Enterobacterales in relation to β-lactamase type and enhancer effect, as tested by BSAC agar dilution. (4th April 2022) - Mushtaq, Shazad; Vickers, Anna; Chaudhry, Aiysha; Woodford, Neil; Livermore, David M
Abstract: Objectives: Combinations of PBP3-active β-lactams with developmental diazabicyclooctanes (DBOs), e.g. zidebactam, remain active against many MBL producers via an enhancer effect. We explored how this activity is affected by inoculum. Materials and methods: MICs of zidebactam and its cefepime and ertapenem combinations (WCK 5222 and WCK 6777, respectively) were determined by BSAC agar dilution at inocula from 3–6 × 10 3 to 3–6 × 10 5 cfu/spot. Isolates, principally Klebsiella spp., were chosen as having previously tested resistant to zidebactam or its cefepime combination, and by β-lactamase type. Results: MICs of zidebactam, tested alone, were strongly inoculum dependent regardless of β-lactamase type; MICs of its cefepime and ertapenem combinations likewise were strongly inoculum dependent—rising ≥32-fold across the inoculum range tested—but only for MBL producers. Combination MICs for isolates with non-MBLs, including those with OXA-48 (where the enhancer effect remains critical for ertapenem/zidebactam) were much less inoculum dependent, particularly for cefepime/zidebactam. MBL producers frequently moved between putative 'susceptible' (MIC ≤ 8 + 8 mg/L) and 'resistant' (MIC > 8 + 8 mg/L) categories according to whether the inoculum was at the high or low end of BSAC's acceptable (1–4 × 10 4 cfu/spot) range. Conclusions: The activity of zidebactam combinations against MBL producers, which strongly depends on the enhancer effect, is inoculum dependent. Animal data suggest consistent in vivo activity even in high-inoculum pneumonia models. Contingent on this being supported by clinical experience, the combination behaviour may be best represented by the MICs obtained at the lower end of BSAC's inoculum range.